2017
DOI: 10.1002/glia.23118
|View full text |Cite
|
Sign up to set email alerts
|

How a radial glial cell decides to become a multiciliated ependymal cell

Abstract: The V-SVZ adult neurogenic niche is located in the wall of the lateral ventricles and contains neural stem cells, with self-renewing and differentiating ability and postmitotic multiciliated ependymal cells, an important structural and trophic component of the niche. The niche is established at postnatal stages from a subpopulation of radial glial cells, determined during embryogenesis. Radial glial cells constitute a heterogeneous population, which give rise, in addition to niche cellular components, to neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 110 publications
(250 reference statements)
0
29
0
3
Order By: Relevance
“…Так, установлено, что взрослая нейрогенная ниша V-SVZ, расположенная в желудочково-субвентрикулярной зоне стенки боковых желудочков, наряду с нервными стволовыми клетками с самообновляющейся и дифференцирующейся способностью содержит также постмитотические многоресничные эпендимальные клетки, являющиеся важным структурным и трофическим компонентом ниши. Ниша формируется в постнатальный период из субпопуляции радиальных глиальных клеток, при этом процесс дифференцировки последних в многоресничные эпендимальные клетки происходит с участием факторов McIdas и GemC1/Lynkeas и активируемых ими сигнальных путей [39] (рисунок 1).…”
Section: фундаментальная и клиническая медицина ®unclassified
“…Так, установлено, что взрослая нейрогенная ниша V-SVZ, расположенная в желудочково-субвентрикулярной зоне стенки боковых желудочков, наряду с нервными стволовыми клетками с самообновляющейся и дифференцирующейся способностью содержит также постмитотические многоресничные эпендимальные клетки, являющиеся важным структурным и трофическим компонентом ниши. Ниша формируется в постнатальный период из субпопуляции радиальных глиальных клеток, при этом процесс дифференцировки последних в многоресничные эпендимальные клетки происходит с участием факторов McIdas и GemC1/Lynkeas и активируемых ими сигнальных путей [39] (рисунок 1).…”
Section: фундаментальная и клиническая медицина ®unclassified
“…This developmental coronary blood vessel differentiation patterning seems to be dependent on the Notch signaling pathway, given that Notch1, 3 and 4 and the Notch ligand DII4 are specifically expressed in arterial endothelial cells and control EphrinB2 expression (Lawson et al, ). Thus, coronary expression of Notch pathway receptors and ligands, which are also present in other stem cell niches (Sailaja et al, ; Seshadri and Qu, ; Kyrousi et al, ), suggests that blood vessels could be a pivotal element of potential CI niches.…”
Section: The Basic Structure Of the Adult CImentioning
confidence: 99%
“…Recent findings have emphasized the role of the geminin family members McIdas (also known as Idas) (Pefani et al, 2011) and geminin coiled-coil domain-containing protein 1 (GMNC; also known as Lynkeas; hereafter referred to as GemC1) (Balestrini et al, 2010), to multiciliate cell fate acquisition and differentiation (reviewed in Arbi et al, 2018;Kyrousi et al, 2016Kyrousi et al, , 2017. GemC1 had initially been identified as a cell cycle regulator, essential for the initiation of DNA replication during the transition from G1 to S phase (Balestrini et al, 2010) but was later shown to constitute a key molecule in the early steps of multiciliate cell differentiation.…”
Section: Introductionmentioning
confidence: 99%